Cost of incorrect application of antithrombotic prophylaxis prior to invasive procedures - Ma Victoria Cuevas; Ignacio Martínez-Sancho; Jana Arribas; Covadonga García-Díaz; Beatriz Cuevas (BMC, 2019)
Abstract Background We analyze the cost of an incorrect application, by the haematologist, of bridging anticoagulation in patients with low-risk atrial fibrillation (AF) needing interruption of treatment prior to a scheduled invasive procedure. Although not recommended, bridging therapy is widely used, resulting in avoidable costs and increased workload. Methods Observational retrospective study. We recorded demographic and clinical data including age, sex, type of procedure, use of bridging therapy with low molecular weight heparin (LMWH), and haemorrhagic complications within 30 days of acenocoumarol withdrawal. Results Acenocoumarol was stopped in 161 patients, 97 (60%) were male and 64 (40%) female. Average age was 76,11 ± 8,45 years. Procedures included: minor surgical intervention 58 (36%), colonoscopy 61 (38%), gastroscopy 11 (7%), breast biopsy 4 (2.5%), prostate biopsy 4 (2.5%), infiltration 5 (3%), and other 18 (11%). All patients received bridging anticoagulation with LMWH (40 mg enoxaparin per day) 3 days before and 3 days after the procedure (6 doses). We used a total of 966 doses, at €4.5 per unit, resulted in €4347 of total cost. No complications occurred in 156 patients (97%). Haemorrhage was observed in 5 cases: 1 major haemorrhage needing 6 days of hospital stay and transfusion, and 4 minor haemorrhages (2 patients needed emergency attendance and 2 required hospital admission for 3 and 2 days, respectively). The cost of emergency care was €237.36, and the cost of hospital stay was €6860.81 (€623.71 per day, for 11 days). The total cost of the incorrect application of the protocol was €11,445.17. Conclusion Guidelines about bridging anticoagulation in low risk AF patients undergoing scheduled invasive procedures were not followed. This practice increments the complications and supposes an increase in costs besides to an inadequate use of the human resources.